Managing the COVID-19 Pandemic as a National Radiation Oncology Centre in Singapore. Issue 7 (July 2020) - Tan, B.F.; Tuan, J.K.L.; Yap, S.P.; Ho, S.Z.; Wang, M.L.C.
Abstract: COVID-19, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), was declared a global pandemic in March 2020. It has impacted the world medically, financially, politically and socially, with countries such as China and Italy adopting a full lockdown of their cities to mitigate the transmission. The current mortality rate is 5.4%, with 1 056 159 people infected worldwide. The disease is reminiscent of SARS in 2002, from which the healthcare system of Singapore has garnered many lessons and applied them in the current climate. As a result of the high transmissibility of the virus, hospitals in Singapore have reduced clinic loads and elective treatments to halt propagation of the virus and also to allow redistribution of healthcare workforce to the frontline. Cancer patients, who are often immunocompromised, are at risk of contracting the disease and becoming seriously ill. At the same time, delaying treatment such as radiotherapy in cancer patients can be detrimental. Here, we describe our experience as a large radiation oncology department in Singapore, including the challenges we encountered and how we managed our patient flow.